Differences in Vital Capacity and Length of a Dive in Dynamics with and without Glossopharyngeal Insufflation in Breath-hold Divers - Sime Zurak; Ivan Belcic; Alen Marosevic (Journal of Anthropology of Sport and Physical Education, 2019)
The purpose of this study was to determine diff erences between vital capacity and length of a dive in dynamics (DYN) with and without glossopharyngeal insuffl ation in breath-hold divers. The sample consisted of 15 elite breath-hold divers (12 male subjects and 3 female subjects) who were in regular training process and members of national team in Croatia. The sample of variables consisted two measures for estimating valuation of vital capacity (VC and VCP) and two measures for determining length of a dive in meters (URON and URONP). All variables have standard their basic statistic parameters and were tested to determine statistically signifi cant diff erences between the vital capacity and length of a dive with and without glossopharyngeal insuffl ation as technique of air packaging. One-sided t- test for dependent samples was used and with results (signifi cance level of p = 0.00) it can be concluded that there is a statistically signifi cant diff erence between vital capacity and length of a dive with and without glossopharyngeal insuffl ation. Technique of packing air (glossopharyngeal insuffl ation) is producing better results for competitors, but with this advantage athletes must be aware of disadvantages of using this technique which can cause injuries to respiratory system and its organs.